Defending dissensus: participatory governance and the politics of water measurement in Montana's Yellowstone River Basin. Issue 6 (1st November 2016) - Anderson, Matthew B.; Hall, Damon M.; McEvoy, Jamie; Gilbertz, Susan J.; Ward, Lucas; Rode, Alyson
ABSTRACT: The role of a particular aspect of collaboration, dissensus, in stimulating critical reconsideration of 'prior appropriation', a historically hegemonic condition related to water rights in the western United States, is examined via a collaborative planning effort in Montana. Consensual support for a water-use measuring proposal was undermined by strong libertarian resistance to governmental regulation, and an unwavering embrace of the status quo . However, based on insights from scholars engaged in the 'post-political' dimensions of contemporary forms of rule – dissensus – understood as the manifestation of consensus-forestalling disagreement articulated between oppositional voices – is revealed as a condition to be actively nurtured, rather than purged. This case reveals how dissensus can open discursive spaces for hegemony-disrupting modes of inquiry, alternative perspectives, and innovative possibilities, even among sanctioned participant voices operating within otherwise established, de politicized governing arenas. The study thus deepens our understanding of the complex political dynamics of participatory water planning.